1994
DOI: 10.4157/grj1984b.67.36
|View full text |Cite
|
Sign up to set email alerts
|

Altitudinal Distribution of Humus Properties of Andisols in Japan

Abstract: Humic properties imparted to Andisols during pedogenesis are resistant to diagenetic alter ation and are preserved in stable enough form to reconstruct the paleoenvironment of the Holocene. Success in the reconstruction of paleoenvironment from soil evidence depends on the fi eld area chosen. By investigating four volcanic areas in Japan, we examined the altitudinal distribution of two soil attributes, humus accumulation and Pg absorption of humic acid, and their regularity to clarify the 'promising area' for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In addition, Numata (1969) reported that based on research performed by the Ministry of Agriculture & Forestry of Japan (1959), M. sinensis grasslands managed by mowing had higher amounts of humus, soil moisture content, and total N than grasslands dominated by Z. japonica or Pleioblastus spp. M. sinensis has been shown to contribute to humus development on mountain slopes and diluvial uplands at Mount Towada (40–500 m asl, 40°28′N, 140°55′E), Mount Akagi (380–1438 m asl, 36°32′N, 139°10′E), and Mount Daisen (180–820 m asl, 35°22N, 133°32E) (Watanabe et al , 1994). Based on chemical and spectroscopic analysis of charred residues of M. sinensis , Shindo et al (1986) determined that humic acids derived from the burning of M. sinensis vegetation contributed to the abundant accumulation of humus in many soils in Japan (Seki, 1934; Kawamura, 1950; Yamane, 1973).…”
Section: Soil‐forming Processes In M Sinensis‐dominated Soilsmentioning
confidence: 99%
“…In addition, Numata (1969) reported that based on research performed by the Ministry of Agriculture & Forestry of Japan (1959), M. sinensis grasslands managed by mowing had higher amounts of humus, soil moisture content, and total N than grasslands dominated by Z. japonica or Pleioblastus spp. M. sinensis has been shown to contribute to humus development on mountain slopes and diluvial uplands at Mount Towada (40–500 m asl, 40°28′N, 140°55′E), Mount Akagi (380–1438 m asl, 36°32′N, 139°10′E), and Mount Daisen (180–820 m asl, 35°22N, 133°32E) (Watanabe et al , 1994). Based on chemical and spectroscopic analysis of charred residues of M. sinensis , Shindo et al (1986) determined that humic acids derived from the burning of M. sinensis vegetation contributed to the abundant accumulation of humus in many soils in Japan (Seki, 1934; Kawamura, 1950; Yamane, 1973).…”
Section: Soil‐forming Processes In M Sinensis‐dominated Soilsmentioning
confidence: 99%
“…In Figure 5 the data for Towada, Nikko, Akagi and Daisen area are quoted from Watanabe et al (1994) and the other data2) are calculated to provide reference data. From this figure, it is recognized that the optimum climatic condi-Fig.…”
Section: Direction Of Modifying the Coefficient (R) Based On The Equivalent Amount Of Humus And Climatic Indicatormentioning
confidence: 99%